Views of the Pharmacists' Role in HPV Vaccinations: A Qualitative Study in Tennessee - Alina Cernasev; Kenneth C. Hohmeier; Oluwafemifola Oyedeji; Kristina W. Kintziger; Tracy M. Hagemann (MDPI AG, 2024)
The Human Papillomavirus (HPV) is a frequently occurring sexually transmitted infection in adults and is associated with various cancers that can affect both males and females. Recently, the Advisory Committee on Immunization Practices (ACIP) expanded its recommendations for the HPV vaccine to include patients aged 27-45 years with shared clinical decision-making. A commonly reported obstacle to receiving the HPV vaccine among adults is a lack of healthcare provider recommendations. Considering the suboptimal HPV vaccine coverage figures and noting that the vast majority of hesitancy research has been conducted among children and adolescents, limited research is available on the adult perception of HPV vaccination in pharmacies. This study focuses on understanding adults' opinions and perceptions regarding the role of pharmacists in the uptake of the HPV vaccine and awareness of its availability in the pharmacy setting. Methods: After receiving approval from the Institutional Review Board (IRB), the qualitative study was initiated using virtual focus groups (FGs). Concepts from the Transtheoretical Model, the Health Belief Model, and the Social Cognitive Theory guided the study design. The corpus of data was collected in 2021 and 2022 by two researchers, and a third party transcribed the FGs to avoid any biases. The data were analyzed using Braun and Clarke's Thematic Analysis. Results: Out of 35 subjects that participated in six FGDs, most identified as female, with ages ranging from 18 to 45 years. The following four themes emerged: (1) HPV vaccine awareness; (2) stigmas leading to reduced education and vaccination rates; (3) education preferences; (4) follow-up in vaccination series reminders and preferences. Conclusion: Participants' views of the HPV vaccine and the ability to receive the vaccine in a pharmacy are influenced by a myriad of factors. Common factors include improved awareness, preferences for educational modalities, avoiding stigmas associated with HPV vaccination, combating gender-focused biases, and preferences for the location of vaccination. These barriers provide opportunities for pharmacists to promote and enhance vaccine uptake.